Panulirus Stimpsoni and checklist of panulirus lobsters in Malaysian waters: Morphological and molecular insights - Wei-Ling Ng; Cheng-Ann Chen; Chui Pin Leaw; Sing Tung Teng; Raymie bin Nurhasan; Tin-Yam Chan (Cambridge University Press, 2024)
Panulirus stimpsoni is restricted to southern China, Vietnam, and Japan but has been rarely reported in tropical Gulf of Thailand. In Malaysia, only six species were previously reported. This study (1) reports the seventh Malaysian species – a new record of P. stimpsoni with morphological and genetic data; (2) establishes a checklist of Malaysian Panulirus species. Surveys from 2021 to 2022 sampled lobsters across Malaysia by SCUBA or from fishermen. Seven species were identified and a modified key of Malaysian species was constructed. The COI gene was used for genetic identification and phylogenetic tree reconstruction with maximum likelihood (ML). The best model was GTR + I + G. The ML tree comprised Clades I and II with sequences clustering by species and strong support. Most Peninsular Malaysian lobsters were P. polyphagus while P. versicolor dominated Sabah. Information on P. stimpsoni’s full fishery potential, distribution, ecology, and biology is limited. Further research is needed to ensure conservation and management as data are only available for six previously reported species. Further studies are required to discover sustainable use approaches for all Panulirus species, particularly P. stimpsoni, given limited ecological understanding